A new variant of the B-dot control for spacecraft magnetic detumbling. (June 2020) - Desouky, Mohammed A.A.; Abdelkhalik, Ossama
Abstract: With using the B-dot control law for magnetic detumbling, there will be no need for angular velocity measurements. The B-dot control law is a torque projection-based controller, however, it is not guaranteed to have the dipole moment orthogonal to the magnetic field, especially as the angular velocity gets smaller during detumbling, resulting in a suboptimal torque vector. This paper presents a new variant of the B-dot control. By computing an equivalent angular velocity, based on the magnetic field data, it is possible to develop a control law that guarantees the magnetic dipole moment to remain in the plane orthogonal to the ambient magnetic field. Using Monte Carlo simulations, the proposed B-dot control is compared to two other variants of B-dot control laws: a simple B-dot control and a recent variable gain B-dot control. The results show that the proposed B-dot control outperforms the other B-dot control laws in terms of the speed of detumbling and the power consumption. Highlights: Spacecraft magnetic detumbling using B-dot law. New variant of B-dot law that is featured by its faster detumbling time and lower power consumption. Numerical computation of the magnetic field derivative using the five-stencil method. Asymptotic Lyapunov stability.